A heating glove based on flexible carbon-based composite film

By adopting flexible carbon-based composite film technology in heating gloves, combined with the design of leaf-like carbon nanotubes and decahydrate borax, the shortcomings of existing heating gloves in terms of flexibility, self-healing and mechanical properties are solved, and efficient, safe and durable heating effects are achieved.

CN118716721BActive Publication Date: 2025-03-14SHENZHEN EIGDAY HEATING LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411089735.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-09
Publication Date
2025-03-14
Estimated Expiration
2044-08-09

AI Technical Summary

Technical Problem

Existing heating gloves have shortcomings in flexibility, self-healing and mechanical properties, which are difficult to meet the needs of high-performance heating gloves.

Method used

The design based on flexible carbon-based composite films is adopted, including self-healing flexible carbon-based electric heating films, flexible carbon-based thermal insulation layer and fluorinated polyurethane fiber membranes, and the self-healing, thermal conductivity and mechanical properties of the material are improved through the unique design of leaf-like carbon nanotubes and the cross-linking effect of decahydrate borax.

Benefits of technology

It significantly improves the self-healing ability, electric heat conversion efficiency and mechanical properties of heating gloves, extends the service life, and ensures the efficient and safe performance of gloves in complex environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118716721B_ABST
    Figure CN118716721B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of electric heating gloves, a heating glove based on a flexible carbon-based composite film, characterized in that it comprises a glove body, which is composed of an outer layer, a heat insulation layer, a self-healing flexible carbon-based electric heating film, a flexible carbon-based heat-conducting insulating layer and an inner layer from the outside to the inside; an elastic band is installed inside the cuff of the glove body for warmth preservation and tightness, a battery bag is provided at the cuff of the glove body, the battery bag is an elastic waterproof fabric, a zipper is provided on one side of the battery bag for easy access, a battery is provided inside the battery bag, the battery is a rechargeable battery, the battery bag is provided with a temperature control module, the temperature control module is provided with a switch and a temperature adjustment button, and the battery and the self-healing flexible carbon-based electric heating film are respectively connected to the temperature control module block through a wire. In particular, the self-healing flexible carbon-based electric heating film solves the problem that the electric heating film in the current electric heating gloves is insufficient in terms of self-healing, flexibility and electric heating performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of electric heating gloves, and in particular to a heating glove based on a flexible carbon-based composite film. Background Art

[0002] In cold winter outdoor adventures, alpine skiing, or industrial operations that require long-term exposure to low temperatures, an efficient and comfortable hand warming solution is particularly important. Against this background, heated gloves came into being. The performance requirements of this type of gloves focus on excellent electrothermal conversion efficiency to ensure that the hands heat up quickly and maintain a constant temperature; at the same time, its flexible design ensures the wearer's hands are flexible and comfortable in complex environments. Therefore, the development of heated gloves not only meets the urgent need for personal warmth under extreme conditions, but also promotes the in-depth application of smart wearable technology in the fields of safety protection and personal health, and has multiple development significances such as improving work efficiency, ensuring personnel safety, and promoting technological innovation.

[0003] At present, the electric heating layer of heating gloves has made a lot of progress, but there are still some shortcomings. (1) The self-healing ability still needs to be further improved to meet the requirements of more demanding use environments. For example, in complex and changeable outdoor environments, frequent friction, stretching and even accidental damage may exceed the repair ability of current electric heating materials, resulting in the degradation of glove performance or even failure. For example, the Chinese patent with publication number CN204483158U discloses an electric heating glove based on heating copper wire. Although the design is advanced, the copper wire lacks self-healing ability, thus affecting the life of the electric heating glove. Therefore, further improving the self-healing efficiency and range and developing electric heating materials that can self-heal under a wider range of conditions are important directions for improving the service life and safety of heating gloves. (2) Electric heating performance is still one of the technical difficulties. Although the current technology has achieved a certain degree of electric heating conversion, there is still room for improvement in terms of rapid response, uniform heating and energy efficiency. Especially in low temperature environments, how to ensure that the gloves quickly reach and maintain a suitable temperature while reducing energy consumption is the key to optimizing electric heating performance. (3) The lack of mechanical properties and flexibility is also a major challenge. As a wearable device, heating gloves need to have good mechanical properties to withstand various stresses in daily use. Existing products still need to be strengthened in terms of tensile strength, tear resistance and wear resistance. Especially under extreme working conditions, such as heavy physical labor or frequent bending of fingers, the insufficient mechanical properties of the gloves may cause damage, affecting the use effect and safety. In order to fill this technical gap, it is necessary to develop a new type of heating gloves so that the electric heating material of the heating gloves has excellent flexibility, self-healing and mechanical properties to meet the needs of high-performance heating gloves. Summary of the invention

[0004] (1) Technical issues solved

[0005] The purpose of the present invention is to provide a heating glove based on a flexible carbon-based composite film to solve the problem that the current heating layer has insufficient performance in terms of flexibility, self-healing and mechanical properties.

[0006] (2) Technical solution

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] A heating glove based on a flexible carbon-based composite film comprises a glove body, wherein the glove body comprises an outer layer, a heat insulating layer, a self-healing flexible carbon-based electric heating film, a flexible carbon-based heat conductive insulating layer and an inner layer from the outside to the inside; the outer layer, the heat insulating layer, the self-healing flexible carbon-based electric heating film, the flexible carbon-based heat conductive insulating layer and the inner layer are connected together by stitches; an elastic band is installed inside the cuff of the glove body for warmth preservation and tight fitting, a battery bag is provided at the cuff of the glove body, the battery bag is made of elastic waterproof fabric, a zipper is provided on one side of the battery bag for easy access, a battery is provided inside the battery bag, the battery is a rechargeable battery, the battery bag is provided with a temperature control module, the temperature control module is provided with a switch and a temperature adjustment button, and the battery and the self-healing flexible carbon-based electric heating film are respectively connected to the temperature control module through wires.

[0009] Furthermore, the self-healing flexible carbon-based electric heating film (13) is prepared from the following components in parts by weight: 25 to 35 parts of polyvinyl alcohol, 25 to 35 parts of poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid), 4 to 9 parts of polyethylene glycol 200, 3 to 7 parts of leaf-shaped carbon nanotubes, 2 to 5 parts of borax decahydrate, and 40 to 60 parts of a mixed solution of methanol and deionized water in a mass ratio of 1:1.

[0010] Furthermore, the mass ratio of the polyvinyl alcohol to the poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) is 1:1.

[0011] Furthermore, the preparation method of the leaf-shaped carbon nanotubes is as follows: in parts by weight, at 0-5°C, 5-10 parts of sodium nitrate and 50-80 parts of concentrated sulfuric acid are mixed evenly in a beaker, then 20-35 parts of multi-walled carbon nanotubes and 4-10 parts of potassium permanganate are added and stirred for 2-4 hours, then the beaker is heated to 25-35°C and stirred for 30-45 minutes, then 100 parts of deionized water are added drop by drop, after the addition is completed, the mixed solution is heated to 85-95°C, and the stirring reaction is continued for 10-20 minutes, and then 3% hydrogen peroxide is dripped into the mixed solution until the gas stops being generated, the product is collected by vacuum filtration, and then the filtered product is washed three times with deionized water, each washing needs to be completely submerged with deionized water. Finally, the washed product is thoroughly dried in a vacuum drying oven at room temperature to obtain leaf-shaped carbon nanotubes.

[0012] The present invention adopts a unique leaf-shaped carbon nanotube design, achieving multiple advantages, especially achieving significant improvements in thermal and electrical conductivity. First, the leaf-shaped carbon nanotubes in the present invention are composed of homogeneous materials, wherein the leaf part is similar to graphene, and the petiole part is similar to carbon nanotubes. Unlike the method of adding graphene or carbon nanotubes alone or simply mixing the two in traditional electric heating materials, the leaf and petiole of the present invention are seamlessly connected to form an integral structure. This design is conducive to the conduction of electrons and phonons inside the material, thereby greatly improving the thermal and electrical conductivity of the material. In contrast, the lack of close bonding between graphene and carbon nanotubes in traditional methods limits the transmission of electrons and phonons, resulting in limited thermal and electrical conductivity. Secondly, the leaf-shaped structure also brings advantages in mechanical properties. The presence of numerous leaves and petioles significantly increases the specific surface area of ​​the material, provides more contact area, and is conducive to the dispersion and transmission of external forces and stresses inside the material. At the same time, this multi-level structure also gives the material good elasticity and impact resistance. When the material is subjected to external force, the leaves can deform, absorb and buffer the impact energy, while the petiole plays the role of supporting and transmitting the load, which together improves the mechanical properties of the material. In summary, the present invention cleverly utilizes the design of leaf-shaped carbon nanotubes, organically combines the advantages of graphene and carbon nanotubes, overcomes the shortcomings of traditional single addition or simple mixing methods, and achieves comprehensive improvements in thermal conductivity, electrical conductivity, mechanical strength, elasticity and impact resistance, showing broad application prospects.

[0013] The multiple design purposes of the self-healing flexible carbon-based electric heating film designed by the present invention are as follows: 1. In terms of self-healing, one of the core advantages of the self-healing flexible carbon-based electric heating film designed by the present invention is its excellent self-healing ability. This feature is achieved by introducing polyvinyl alcohol as a matrix material and cleverly using borax decahydrate as a cross-linking agent. The abundant hydroxyl groups on the polyvinyl alcohol molecular chain provide the possibility for self-repair, and the addition of borax decahydrate further enhances the self-repairing performance of the material through a cross-linking reaction. When the film is damaged by the outside world, the cross-linking structure between borax decahydrate and polyvinyl alcohol can respond quickly, and the self-repair of the damaged area can be achieved through rearrangement and cross-linking between molecules, thereby extending the service life of the film and improving its reliability. In addition, by adjusting the content of borax decahydrate, the speed and effect of self-repair can be finely controlled to meet the needs of different application scenarios. 2. In terms of electric heating, the present invention uses leaf-shaped carbon nanotubes as conductive fillers. This unique structure gives the film excellent electric-heat conversion efficiency and stability. Leaf-shaped carbon nanotubes have a large specific surface area and excellent electrical conductivity, and can quickly generate heat at a lower voltage to achieve efficient electric-heat conversion. At the same time, its unique morphological structure helps to form a complex conductive network inside the film, improving the uniformity and efficiency of charge transfer. In addition, through close integration with the polyvinyl alcohol matrix, the leaf-shaped carbon nanotubes can be stably dispersed in the film to avoid shedding or aggregation during use, thereby ensuring the long-term stability of the electrothermal performance. In addition, as a solvent with a high dielectric constant, methanol plays a key role in improving conductivity due to its unique physical and chemical properties. Specifically, methanol can effectively shield the charge interaction between the positively charged poly(3,4-ethylenedioxythiophene) chain and the negatively charged sodium polystyrene sulfonate. This shielding effect reduces the obstruction of the Coulomb force, thereby promoting the migration of charge carriers. The slow evaporation of methanol promotes the rearrangement and densification of the components inside the film, effectively reducing pores and defects, thereby bringing better film uniformity. This improvement in uniformity not only helps the continuous transmission of charge carriers in the film, but also reduces the resistance loss caused by structural unevenness, further improving the conductivity. 3. In terms of flexibility, after the leaf-shaped carbon nanotubes are incorporated into the composite material, its flexibility is significantly improved. This is mainly due to the unique morphological structure of leaf-shaped carbon nanotubes: the broad "leaf" part effectively disperses stress, while the slender "petiole" part provides good flexibility. These nanotubes are closely integrated with the matrix material to form a strong interface, and enhance the deformation ability and recovery of the material through network-like interweaving, thus giving the composite material excellent flexibility while maintaining strength.

[0014] Further, the preparation method of the flexible carbon-based thermally conductive insulating layer is as follows: by weight, 4 to 9 parts of fluorinated graphene and 100 parts of N-methylpyrrolidone are ultrasonically treated for 1 to 2 hours to obtain a fluorinated graphene suspension for use. Then 10 to 16 parts of polyvinyl alcohol and 80 to 120 parts of deionized water are mixed and heated to 70 to 85°C, and stirred for 5 to 10 minutes to obtain a polyvinyl alcohol aqueous solution for use. Then the uniformly dispersed fluorinated graphene suspension is vacuum filtered to remove N-methylpyrrolidone to obtain a carbon-based film, and then the polyvinyl alcohol aqueous solution is poured on the carbon-based film in three times, and the polyvinyl alcohol is infiltrated into the carbon-based film under vacuum pressure by vacuum filtration. Then, after the filtered carbon-based film is completely dried in a vacuum drying oven, the carbon-based film is hot-pressed at a temperature of 200 to 230°C and a pressure of 5 to 20 MPa for 5 to 10 minutes to finally obtain a flexible carbon-based thermally conductive insulating layer.

[0015] Furthermore, the preparation method of the fluorinated graphene is as follows: by weight, 3 to 6 parts of graphene oxide and 30 to 60 parts of polyvinylidene fluoride are separated in a crucible by a copper mesh, with graphene oxide on the top and polyvinylidene fluoride on the bottom, and heated to 350 to 400° C. in an air environment, and kept warm for 2 to 4 hours to obtain a crude fluorinated graphene product, and then the crude fluorinated graphene product is washed three times with N-methylpyrrolidone, each washing needs to completely submerge the crude fluorinated graphene product, and finally dried completely in a vacuum drying phase at room temperature to obtain fluorinated graphene.

[0016] Furthermore, the mass ratio of the graphene oxide to polyvinylidene fluoride is 1:10.

[0017] Furthermore, the fluorinated graphene contains 5 to 7.5% fluorine atoms.

[0018] The present invention adopts a flexible carbon-based thermally conductive insulating layer as the insulating layer of the electric heating gloves, aiming to significantly improve the thermal conductivity and safety performance of the electric heating gloves. The design cleverly combines the ultra-high in-plane thermal conductivity and electrical insulation properties of fluorinated graphene, as well as the flexibility of the polyvinyl alcohol matrix, to jointly construct a new type of nanocomposite material. Specifically, the present invention uses vacuum filtration technology to evenly disperse the F-graphene obtained by exfoliation of commercial fluorinated graphite in a suspension assisted by polyvinyl alcohol, and prepares a self-supporting flexible composite film through a carefully controlled process. In this process, the fluorinated graphene sheets are well arranged and distributed, thereby ensuring that the composite film has both excellent thermal conductivity and excellent electrical insulation properties while maintaining a high filler content. As the thermally conductive insulating layer of the electric heating gloves, the composite film not only realizes the rapid and uniform conduction of heat inside the gloves, effectively improving the heating efficiency and wearing comfort, but also completely eliminates the potential safety hazards caused by conductivity through its electrical insulation properties, providing users with a safer and more reliable use experience. In addition, the introduction of polyvinyl alcohol gives this layer of material excellent flexibility, allowing it to fit the contour of the hand closely and meet the high flexibility requirements of wearable devices. In summary, the design of the flexible carbon-based thermal conductive insulating layer of the present invention achieves a perfect fusion of thermal conductivity, insulation and flexibility in the field of electric heating gloves technology, showing significant technical innovation and practical application value, and providing strong support for the further development of related fields.

[0019] The present invention also specifically limits the fluorine atomic percentage of fluorine in fluorinated graphene to 5-7.5%, the main purpose of which is to increase the insulation and maintain the flexibility of graphene. Specifically, fluorine atoms are a highly electronegative element, and their presence can change the electronic structure of graphene. The introduction of fluorine atoms in fluorinated graphene changes the structure of graphene, forming a barrier structure that hinders the free conduction of electrons. This structure can effectively prevent the movement of electrons in the material, thereby improving the insulation performance of fluorinated graphene. In addition, graphene is a high thermal conductivity flexible material, so it is beneficial to increase the thermal conductivity and flexibility of the flexible carbon-based thermal conductive insulating layer.

[0020] Furthermore, the outer layer is a fluorinated polyurethane fiber membrane, and its preparation method is as follows: after 2 to 4 parts of silver nitrate and 100 parts of dimethylacetamide are mixed evenly by weight, 15 to 30 parts of fluorinated polyurethane prepolymer are added and stirred at 200 to 350 rpm for 4 to 6 hours to obtain a mixed solution, which is then sent into a syringe with a capillary tip, the anode of the high-voltage power supply is connected to the syringe needle tip, and the cathode is connected to the floor drum. The fluorinated polyurethane fiber membrane is prepared by an electrospinning process, wherein the process parameters of the electrospinning are: an applied voltage of 40 to 50 kV, a constant infusion rate of 1 to 2.5 mL / h, a receiving distance of 20 to 25 cm, an ambient temperature of 20 to 25°C, and a relative humidity of 70 to 80%.

[0021] Furthermore, the preparation method of the fluorinated polyurethane prepolymer is as follows: in parts by weight, in a nitrogen environment, 10 to 18 parts of polytetrahydrofuran, 20 to 30 parts of 4,4'-methylenebis(phenyl isocyanate) and 18 to 25 parts of dimethylformamide are added to a four-necked flask, and stirred at 160 to 240 rpm for 30 to 60 minutes at 55 to 65°C to obtain a transparent and uniform solution, and then 2 to 5 parts of triethylene glycol chain extender are added thereto, and the stirring reaction is continued at 60 to 70°C for 1 to 3 hours, and finally 15 to 22 parts of perfluorobutylethanol and 7 to 14 parts of dimethylformamide are added to the flask, and stirring is continued for 2 to 4 hours to obtain a fluorinated polyurethane prepolymer.

[0022] The present invention uses fluorinated polyurethane fiber membrane as the outer layer of electric heating gloves, aiming to achieve multiple goals: first, from the wear resistance point of view, the fiber membrane gives the material surface a higher hardness and toughness through a special molecular chain structure, thereby effectively resisting external wear and extending the service life of the gloves. Secondly, in terms of breathability and waterproofness, fluorine atoms can form a dense hydrophobic layer on the surface of the fiber membrane due to their extremely low surface energy, significantly reducing the surface free energy of the material, making it difficult for water to wet and penetrate the membrane surface, achieving an excellent waterproof effect. At the same time, the microporous structure inside the fiber membrane allows air and water vapor to flow freely, keeping the hands dry and comfortable. This unique breathable and waterproof performance is due to the excellent combination of the hydrophobic effect of the fluorine element and the microporous structure of the fiber membrane. Furthermore, from the perspective of flexibility, the fluorinated polyurethane fiber membrane uses a highly elastic polyurethane material, and through a special processing technology, the fiber membrane has both good flexibility and sufficient strength, ensuring that the gloves provide sufficient support and protection while fitting the hands. In addition, the introduction of fluorine does not significantly affect the flexibility of the fiber membrane, but instead helps to improve the overall performance of the fiber membrane due to its excellent chemical stability. In terms of mechanics, there is a strong interaction force between the polymer chains of the fluorinated polyurethane fiber membrane, which gives the material excellent tensile strength and tear strength. This allows the gloves to effectively resist deformation and breakage when subjected to external forces, protecting the safety of the hands. Finally, from the antibacterial aspect, antibacterial ingredients such as silver ions can be embedded in the fiber membrane. The synergistic effect of these antibacterial ingredients and the fluorine element can further destroy the bacterial cell structure and inhibit bacterial growth and reproduction, thereby ensuring hand hygiene. In summary, the fluorinated polyurethane fiber membrane brings multiple performance improvements to the electric heating gloves, such as wear resistance, breathability and waterproofness, flexibility, mechanical support and antibacterial, through the hydrophobic effect of the fluorine element and its perfect combination with polyurethane materials, meeting a variety of practical needs.

[0023] Furthermore, the thermal insulation layer is a polyimide aerogel, and its preparation method is as follows: in parts by weight, at 0°C, 4 to 9 parts of 4,4'-diaminodiphenyl ether, 4 to 9 parts of pyromellitic anhydride and 100 parts of N-methylpyrrolidone are mixed evenly, 4 to 8 parts of short-cut polyimide nanofibers are added, and then stirred at 300 to 450 rpm for 3 to 6 hours to obtain a uniformly dispersed solution, and then 30 to 45 parts of propionic anhydride and 30 to 45 parts of pyridine are added and stirred thoroughly, and then the solution is cast into a polytetrafluoroethylene mold with a scraper. After gelation, a polyimide aerogel is obtained.

[0024] Furthermore, the preparation method of the short-cut polyimide nanofiber is as follows: by weight, 10 to 16 parts of 4,4'-diaminodiphenyl ether, 10 to 16 parts of pyromellitic anhydride and 150 parts of dimethylacetamide are mixed evenly and added into an electrospinning syringe, and polyimide fibers are obtained by an electrospinning process, wherein the process parameters of the electrospinning are: a spinning voltage of 90 to 105 kV, an electrospinning speed of 1.5 to 3 mL / h, and after the spinning is completed, the spinning is treated at 300 to 350° C. for 1 to 3 hours to obtain polyimide nanofibers, and finally the polyimide nanofibers are cut into short-cut polyimide nanofibers with a cutter.

[0025] Furthermore, the length of the short-cut polyimide nanofibers is 10 to 60 μm.

[0026] The present invention uses polyimide aerogel film as the thermal insulation layer of the electric heating gloves, aiming to achieve the optimization of multiple performances. By precisely regulating the chemical compatibility and interfacial bonding strength between PI nanofibers and PI aerogel matrix, the present invention successfully transforms the brittleness of the aerogel film into high flexibility, so that the gloves have excellent flexibility and comfort while maintaining excellent thermal insulation performance, and can adapt to flexible operations in various complex environments. At the same time, the reinforcing effect of PI nanofibers significantly improves the mechanical properties of the aerogel film, enabling it to withstand greater stretching and bending, and extending the service life of the gloves. More importantly, its unique nanoporous structure effectively blocks the transfer of heat, achieves an efficient thermal insulation effect, and provides a solid thermal protection barrier for the hands. In summary, the PI nanofiber cross-linked PI aerogel film has become an ideal choice for high-end thermal protection materials such as electric heating gloves due to its excellent flexibility, mechanical strength and thermal insulation performance.

[0027] The present invention also specifically limits the length of the short-cut polyimide nanofibers to 10 to 60 μm. The purpose of this design is: first, from the perspective of thermal insulation performance, the length of the short-cut polyimide nanofibers is selected within this range, which helps to form a more compact and uniform nanoporous network structure. This structure can more effectively block the heat transfer path, reduce thermal conductivity, and thus provide more excellent thermal insulation performance. At the same time, the short-cut design of the nanofibers reduces the mutual entanglement between the fibers, improves the uniformity of the dispersion of the fibers in the aerogel matrix, and further enhances the thermal insulation effect. Secondly, from the perspective of flexibility, the length of the short-cut polyimide nanofibers is moderate, which not only maintains the rigidity of the fibers to provide the necessary mechanical support, but also avoids the brittleness and difficulty in bending that may be caused by overly long fibers. This design enables the aerogel film to have excellent flexibility and bendability while maintaining high strength, which adapts to the use requirements of gloves in different bending states. Furthermore, from the perspective of mechanical properties, the addition of short-cut polyimide nanofibers significantly enhances the tensile strength and tear resistance of the aerogel film. Fibers of this length can form a good three-dimensional network structure in the matrix, and through the mutual entanglement and interfacial bonding between the fibers, they can effectively transmit and disperse external forces, thereby improving the overall mechanical properties of the material. This makes the gloves more durable during use, able to withstand greater tensile and bending stresses without being easily damaged. In summary, the present invention limits the length of the chopped polyimide nanofibers to 10 to 60 μm, which is a reasonable design based on comprehensive considerations of thermal insulation, flexibility and mechanical properties. This design not only optimizes the various properties of the aerogel film, but also improves the overall use effect of the electric heating gloves, meeting the strict requirements for high-end thermal protection materials.

[0028] Furthermore, the inner layer is woven from modal fibers.

[0029] Modal fiber, as the inner layer of gloves, demonstrates extraordinary superiority: its extremely soft touch makes it extremely comfortable to wear; its excellent moisture absorption and perspiration ability keeps hands dry and healthy; at the same time, it balances breathability and warmth to prevent stuffiness and cold; and its environmentally friendly characteristics highlight the concept of green living.

[0030] This heating glove adopts innovative flexible carbon-based composite film technology, from the wear-resistant and waterproof outer layer to the comfortable and skin-friendly inner layer, which is progressive layer by layer to form an efficient thermal insulation system. Its feature is the self-healing flexible carbon-based electric heating film, which not only heats quickly and evenly, but also has self-repair ability to extend the service life. With a built-in temperature control module, users can flexibly adjust the temperature to meet personalized needs. The battery bag is made of elastic waterproof fabric and is equipped with a convenient zipper design to ensure that the battery is safely stored and easy to access. In addition, rechargeable batteries are used, which are environmentally friendly and energy-saving, and can be replenished anytime and anywhere. The cuffs of the gloves are equipped with elastic bands to enhance warmth and tightness, and the layers are connected by fine stitching to ensure a stable and durable structure. In summary, this heating glove solution brings users an unprecedented comfortable experience with its efficient, intelligent, safe and humanized design.

[0031] (3) Beneficial technical effects

[0032] The electric heating gloves designed by the present invention achieve the comprehensive performance of efficient warmth preservation, comprehensive safety protection, and extreme comfort and durability through the carefully constructed multi-layer structure and the synergistic effect between them. The specific excellent effects are as follows:

[0033] First, the core heating layer uses a self-healing flexible carbon-based electric heating film. Its leaf-shaped carbon nanotube design combines the excellent conductivity of graphene with the excellent thermal conductivity of carbon nanotubes, achieving a double leap in electric-thermal conversion efficiency and mechanical properties. In addition, the introduction of the self-healing mechanism not only improves the mechanical strength and conductivity of the film, but also significantly extends its service life, giving the gloves efficient, durable and flexible heating characteristics, demonstrating significant technical innovation and application advantages.

[0034] Secondly, the introduction of the flexible carbon-based thermally conductive insulating layer, through the excellent combination of fluorinated graphene and polyvinyl alcohol, not only conducts heat efficiently, improves wearing comfort and heating efficiency, but also completely eliminates the risk of electrical conduction, ensuring absolute safety in use. The precise control of the fluorine content (5-7.5%) further enhances the insulation performance while retaining the flexibility of graphene, achieving triple optimization of thermal conductivity, insulation and flexibility, bringing a major breakthrough in the field of electric heating gloves.

[0035] The present invention uses polyimide aerogel film as the heat insulation layer of the electric heating gloves, and achieves a perfect combination of high flexibility, strong heat insulation and durability by optimizing the interface between PI nanofibers and aerogel matrix, so as to adapt to operations in complex environments. Specially designed short PI nanofibers (10-60μm) enhance the heat insulation effect, improve flexibility and mechanical properties, and ensure the durability of the gloves.

[0036] Finally, the outer layer uses a fluorinated polyurethane fiber membrane, which integrates multiple excellent properties such as wear resistance, waterproof breathability, flexibility, mechanical support and antibacterial, thanks to its unique molecular chain structure, the hydrophobic effect of fluorine atoms and the breathable design of the microporous structure. This design not only extends the service life of the gloves, but also ensures dryness, comfort and hand hygiene during wearing, providing users with a full range of high-quality experience.

[0037] In summary, the electric heating gloves of the present invention achieve an excellent combination of efficient warmth preservation, comprehensive safety protection, and extreme comfort and durability through the careful design and synergy of the multi-layer structure. In particular, the core of the electric heating gloves adopts a self-healing flexible carbon-based electric heating film, and the leaf-shaped carbon nanotubes combine the excellent conductivity of graphene and the excellent thermal conductivity of carbon nanotubes, which not only achieves a double leap in electrothermal conversion efficiency and thermal conductivity, but also significantly improves the durability and reliability of the gloves through the self-healing mechanism. The self-healing ability means that the gloves can automatically repair themselves when they suffer minor damage, reducing performance degradation or failure caused by damage, thereby extending the service life and reducing maintenance costs, showing excellent technical innovation and application value, and providing a new solution for electric heating gloves. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is a front view of a heating glove based on a flexible carbon-based composite film proposed by the present invention.

[0039] Figure 2 for Figure 1 Cross-sectional view of the glove body at A.

[0040] Figure 3 This is a transmission electron microscope (TEM) photograph of the leaf-shaped carbon nanotubes of the self-healing flexible carbon-based electrothermal film for gloves prepared in Example 1 of the present invention.

[0041] Figure 4 The self-healing flexible carbon-based electrothermal film for gloves prepared in Example 1 of the present invention is used as a conductor of a light-emitting diode in a series circuit when it is not stretched.

[0042] Figure 5 The self-healing flexible carbon-based electrothermal film of the gloves prepared in Example 1 of the present invention is in a stretched state and serves as a conductor of a light-emitting diode in a series circuit.

[0043] Figure 6 The self-healing flexible carbon-based electrothermal film of the gloves prepared in Example 1 of the present invention is cut and disconnected to serve as a conductor of the light-emitting diode in the series circuit.

[0044] Figure 7 The self-healing flexible carbon-based electrothermal film of the gloves prepared in Example 1 of the present invention is used as a conductor of a light-emitting diode in a series circuit after being disconnected and self-healed.

[0045] Explanation of the accompanying drawings: 1. Glove body; 11. Outer layer; 12. Thermal insulation layer; 13. Self-healing flexible carbon-based electric heating film; 14. Flexible carbon-based thermal conductive insulation layer; 15. Inner layer; 2. Elastic band; 3. Battery bag; 4. Zipper; 6. Temperature control module. DETAILED DESCRIPTION

[0046] To make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.

[0047] In the case of not specifying specific conditions, the operation in the embodiment is carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not indicated, are all common products on the market. The parts not mentioned in the technical content of the present invention will be processed with reference to the prior art. Unless otherwise specified, the following examples and comparative examples will be tested in parallel and use the same processing steps and parameters. Table 1 shows the reagents required for the examples and comparative examples and the corresponding purchasing companies.

[0048] Table 1 Reagents required for the examples and comparative examples and the corresponding purchasing companies

[0049]

[0050]

[0051] Embodiment 1:

[0052] See also Figure 1-2 The present invention provides a technical solution: a heating glove based on a flexible carbon-based composite film, comprising a glove body 1, the glove body 1 is composed of an outer layer 11, a heat insulation layer 12, a self-healing flexible carbon-based electric heating film 13, a flexible carbon-based thermal conductive insulating layer 14 and an inner layer 15 from the outside to the inside; the outer layer 11, the heat insulation layer 12, the self-healing flexible carbon-based electric heating film 13, the flexible carbon-based thermal conductive insulating layer 14 and the inner layer 15 are connected together by stitches; an elastic band 2 is installed inside the cuff of the glove body 1 for warmth preservation and tightness, a battery bag 3 is provided at the cuff of the glove body 1, the battery bag 3 is an elastic waterproof fabric, a 4 is provided on one side of the battery bag 3 for easy access, a battery 5 is provided inside the battery bag 3, and the battery 5 is a rechargeable battery, a temperature control module 6 is provided on the back of the glove body 1, the temperature control module 6 is provided with a switch and a temperature adjustment button, and the battery 5 and the self-healing flexible carbon-based electric heating film 13 are respectively connected to the temperature control module 6 through wires.

[0053] The self-healing flexible carbon-based electric heating film (13) is prepared from the following components in parts by weight: 25 parts of polyvinyl alcohol, 25 parts of poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid), 4 parts of polyethylene glycol 200, 3 parts of leaf-shaped carbon nanotubes, 2 parts of borax decahydrate, and 40 parts of a mixed solution of methanol and deionized water in a mass ratio of 1:1.

[0054] The preparation method of leaf-shaped carbon nanotubes in this embodiment is as follows: in parts by weight, 5 parts of sodium nitrate and 50 parts of concentrated sulfuric acid are mixed evenly in a beaker at 0°C, and then 20 parts of multi-walled carbon nanotubes and 4 parts of potassium permanganate are added and stirred for 2 hours, and then the beaker is heated to 25°C and stirred for 30 minutes, and then 100 parts of deionized water are added drop by drop. After the addition is completed, the mixed solution is heated to 85°C, and the stirring reaction is continued for 10 minutes. Subsequently, 3% hydrogen peroxide is dripped into the mixed solution until gas stops being generated, and the product is collected by vacuum filtration, and then the filtered product is washed three times with deionized water, and each washing needs to completely submerge the filtered product with deionized water, and finally the washed product is thoroughly dried in a vacuum drying oven at room temperature to obtain leaf-shaped carbon nanotubes.

[0055] The preparation method of the flexible carbon-based thermally conductive insulating layer 14 is as follows: by weight, 4 parts of fluorinated graphene and 100 parts of N-methylpyrrolidone are ultrasonically treated for 1 hour to obtain a fluorinated graphene suspension for use. Then, 10 parts of polyvinyl alcohol and 80-120 parts of deionized water are mixed and heated to 70°C, and stirred for 5 minutes to obtain a polyvinyl alcohol aqueous solution for use. Then, the uniformly dispersed fluorinated graphene suspension is vacuum filtered to remove N-methylpyrrolidone to obtain a carbon-based film, and then the polyvinyl alcohol aqueous solution is poured on the carbon-based film in three times, and the polyvinyl alcohol is infiltrated into the carbon-based film under vacuum pressure by vacuum filtration. Then, after the filtered carbon-based film is completely dried in a vacuum drying oven, the carbon-based film is hot-pressed at a temperature of 200°C and a pressure of 5MPa for 5 minutes to finally obtain a flexible carbon-based thermally conductive insulating layer 14.

[0056] The preparation method of fluorinated graphene in this embodiment is as follows: by weight, 3 parts of graphene oxide and 30 parts of polyvinylidene fluoride are separated in a crucible by a copper mesh, with graphene oxide on the top and polyvinylidene fluoride on the bottom, and heated to 350° C. in an air environment and kept warm for 2 to 4 hours to obtain a crude fluorinated graphene product, and then the crude fluorinated graphene product is washed three times with N-methylpyrrolidone, each washing needs to completely submerge the crude fluorinated graphene product, and finally dried completely in a vacuum drying phase at room temperature to obtain fluorinated graphene.

[0057] In this embodiment, the fluorinated graphene contains 5 to 7.5% fluorine atoms.

[0058] In this embodiment, the outer layer 11 is a fluorinated polyurethane fiber membrane, and its preparation method is as follows: after evenly mixing 2 parts of silver nitrate and 100 parts of dimethylacetamide by weight, 15 parts of fluorinated polyurethane prepolymer are added and stirred at 200 rpm for 4 hours to obtain a mixed solution, which is then fed into a syringe with a capillary tip, the anode of the high-voltage power supply is connected to the syringe needle tip, and the cathode is connected to the floor drum. The fluorinated polyurethane fiber membrane is prepared by an electrospinning process, wherein the process parameters of the electrospinning are: an applied voltage of 40 kV, a constant infusion rate of 1 mL / h, a receiving distance of 20 cm, an ambient temperature of 20°C, and a relative humidity of 70%.

[0059] The preparation method of the fluorinated polyurethane prepolymer in this embodiment is as follows: in parts by weight, 10 parts of polytetrahydrofuran, 20 parts of 4,4'-methylenebis(phenyl isocyanate) and 18 parts of dimethylformamide are added to a four-necked flask under a nitrogen environment, and stirred at 160 rpm for 30 minutes at 55°C to obtain a transparent and uniform solution, and then 2 parts of triethylene glycol chain extender are added thereto, and the stirring reaction is continued at 60°C for 1 hour, and finally 15 parts of perfluorobutylethanol and 7 parts of dimethylformamide are added to the flask, and stirring is continued for 2 hours to obtain a fluorinated polyurethane prepolymer.

[0060] In this embodiment, the heat insulating layer 12 is a polyimide aerogel, and its preparation method is as follows: in parts by weight, at 0°C, 4 parts of 4,4'-diaminodiphenyl ether, 4 parts of pyromellitic anhydride and 100 parts of N-methylpyrrolidone are mixed evenly, 4 to 8 parts of short-cut polyimide nanofibers are added, and then stirred at 300 rpm for 3 hours to obtain a uniformly dispersed solution, and then 30 parts of propionic anhydride and 30 parts of pyridine are added and stirred thoroughly, and then the solution is cast into a polytetrafluoroethylene mold with a scraper. After gelation, polyimide aerogel is obtained.

[0061] The preparation method of short-cut polyimide nanofibers in this embodiment is as follows: 10 parts of 4,4'-diaminodiphenyl ether, 10 parts of pyromellitic anhydride and 150 parts of dimethylacetamide are mixed evenly by weight and added into an electrospinning syringe to obtain polyimide fibers by an electrospinning process, wherein the process parameters of the electrospinning are as follows: the spinning voltage is 90 kV and the electrospinning speed is 1.5 mL / h. After the spinning is completed, the fibers are treated at 300°C for 1 hour to obtain polyimide nanofibers, and finally the polyimide nanofibers are cut into short-cut polyimide nanofibers with a cutter.

[0062] In this embodiment, the length of the short-cut polyimide nanofibers is 10 μm.

[0063] In this embodiment, the inner layer 15 is woven from modal fibers.

[0064] Example 2

[0065] See also Figure 1-2 The present invention provides a technical solution: a heating glove based on a flexible carbon-based composite film, comprising a glove body 1, the glove body 1 is composed of an outer layer 11, a heat insulation layer 12, a self-healing flexible carbon-based electric heating film 13, a flexible carbon-based thermal conductive insulating layer 14 and an inner layer 15 from the outside to the inside; the outer layer 11, the heat insulation layer 12, the self-healing flexible carbon-based electric heating film 13, the flexible carbon-based thermal conductive insulating layer 14 and the inner layer 15 are connected together by stitches; an elastic band 2 is installed inside the cuff of the glove body 1 for warmth preservation and tightness, a battery bag 3 is provided at the cuff of the glove body 1, the battery bag 3 is an elastic waterproof fabric, a 4 is provided on one side of the battery bag 3 for easy access, a battery 5 is provided inside the battery bag 3, and the battery 5 is a rechargeable battery, a temperature control module 6 is provided on the back of the glove body 1, the temperature control module 6 is provided with a switch and a temperature adjustment button, and the battery 5 and the self-healing flexible carbon-based electric heating film 13 are respectively connected to the temperature control module 6 through wires.

[0066] The self-healing flexible carbon-based electric heating film 13 is prepared from the following components in parts by weight: 28 parts of polyvinyl alcohol, 28 parts of poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid), 5 parts of polyethylene glycol 200, 4 parts of leaf-shaped carbon nanotubes, 3 parts of borax decahydrate, and 45 parts of a mixed solution of methanol and deionized water in a mass ratio of 1:1.

[0067] The preparation method of leaf-shaped carbon nanotubes in this embodiment is as follows: in parts by weight, 6 parts of sodium nitrate and 60 parts of concentrated sulfuric acid are mixed evenly in a beaker at 2°C, and then 25 parts of multi-walled carbon nanotubes and 6 parts of potassium permanganate are added and stirred for 3 hours, and then the beaker is heated to 30°C and stirred for 35 minutes, and then 100 parts of deionized water are added drop by drop. After the addition is completed, the mixed solution is heated to 89°C, and the stirring reaction is continued for 12 minutes. Subsequently, 3% hydrogen peroxide is dripped into the mixed solution until gas stops being generated, and the product is collected by vacuum filtration, and then the filtered product is washed three times with deionized water, and each washing needs to completely submerge the filtered product with deionized water, and finally the washed product is thoroughly dried in a vacuum drying oven at room temperature to obtain leaf-shaped carbon nanotubes.

[0068] The preparation method of the flexible carbon-based thermally conductive insulating layer 14 is as follows: by weight, 5 parts of fluorinated graphene and 100 parts of N-methylpyrrolidone are ultrasonically treated for 1.5 hours to obtain a fluorinated graphene suspension for use. Then, 12 parts of polyvinyl alcohol and 90 parts of deionized water are mixed and heated to 75°C, and stirred for 6 minutes to obtain a polyvinyl alcohol aqueous solution for use. Then, the uniformly dispersed fluorinated graphene suspension is vacuum filtered to remove N-methylpyrrolidone to obtain a carbon-based film, and then the polyvinyl alcohol aqueous solution is poured on the carbon-based film three times. By vacuum filtration, polyvinyl alcohol is infiltrated into the carbon-based film under vacuum pressure conditions, and then the filtered carbon-based film is completely dried in a vacuum drying oven, and then the carbon-based film is hot-pressed at a temperature of 210°C and a pressure of 15MPa for 6 minutes to finally obtain a flexible carbon-based thermally conductive insulating layer 14.

[0069] The preparation method of fluorinated graphene in this embodiment is as follows: 4 parts of graphene oxide and 40 parts of polyvinylidene fluoride are separated by a copper mesh in a crucible, with graphene oxide on the top and polyvinylidene fluoride on the bottom, and heated to 360°C in an air environment and kept warm for 3 hours to obtain a crude fluorinated graphene product, and then the crude fluorinated graphene product is washed three times with N-methylpyrrolidone, each washing needs to completely submerge the crude fluorinated graphene product, and finally dried completely in a vacuum drying phase at room temperature to obtain fluorinated graphene.

[0070] In this embodiment, the fluorinated graphene contains 6% fluorine atom.

[0071] In this embodiment, the outer layer 11 is a fluorinated polyurethane fiber membrane, and its preparation method is as follows: after evenly mixing 3 parts of silver nitrate and 100 parts of dimethylacetamide by weight, 20 parts of fluorinated polyurethane prepolymer are added and stirred at 250 rpm for 5 hours to obtain a mixed solution, which is then fed into a syringe with a capillary tip, the anode of the high-voltage power supply is connected to the syringe needle tip, and the cathode is connected to the floor drum. The fluorinated polyurethane fiber membrane is prepared by an electrospinning process, wherein the process parameters of the electrospinning are: an applied voltage of 42 kV, a constant infusion rate of 1.5 mL / h, a receiving distance of 22 cm, an ambient temperature of 22°C, and a relative humidity of 72%.

[0072] The preparation method of the fluorinated polyurethane prepolymer in this embodiment is as follows: in parts by weight, 12 parts of polytetrahydrofuran, 23 parts of 4,4'-methylenebis(phenyl isocyanate) and 20 parts of dimethylformamide are added to a four-necked flask under a nitrogen environment, and stirred at 180 rpm for 40 minutes at 58°C to obtain a transparent and uniform solution, and then 3 parts of triethylene glycol chain extender are added thereto, and the stirring reaction is continued at 63°C for 2 hours, and finally 17 parts of perfluorobutylethanol and 10 parts of dimethylformamide are added to the flask, and stirring is continued for 3 hours to obtain a fluorinated polyurethane prepolymer.

[0073] In this embodiment, the heat insulating layer 12 is a polyimide aerogel, and its preparation method is as follows: in parts by weight, at 0°C, 5 parts of 4,4'-diaminodiphenyl ether, 5 parts of pyromellitic anhydride and 100 parts of N-methylpyrrolidone are mixed evenly, 4 to 8 parts of short-cut polyimide nanofibers are added, and then stirred at 350 rpm for 3 to 6 hours to obtain a uniformly dispersed solution, and then 35 parts of propionic anhydride and 35 parts of pyridine are added and stirred thoroughly, and then the solution is cast into a polytetrafluoroethylene mold with a scraper. After gelation, polyimide aerogel is obtained.

[0074] The preparation method of short-cut polyimide nanofibers in this embodiment is as follows: 12 parts of 4,4'-diaminodiphenyl ether, 12 parts of pyromellitic anhydride and 150 parts of dimethylacetamide are mixed evenly by weight and added into an electrospinning syringe to obtain polyimide fibers by an electrospinning process, wherein the process parameters of the electrospinning are as follows: the spinning voltage is 95 kV and the electrospinning speed is 2 mL / h. After the spinning is completed, the fibers are treated at 320°C for 2 hours to obtain polyimide nanofibers, and finally the polyimide nanofibers are cut into short-cut polyimide nanofibers with a cutter.

[0075] In this embodiment, the length of the short-cut polyimide nanofibers is 20 μm.

[0076] In this embodiment, the inner layer 15 is woven from modal fibers.

[0077] Example 3

[0078] See also Figure 1-2 The present invention provides a technical solution: a heating glove based on a flexible carbon-based composite film, comprising a glove body 1, the glove body 1 is composed of an outer layer 11, a heat insulation layer 12, a self-healing flexible carbon-based electric heating film 13, a flexible carbon-based thermal conductive insulating layer 14 and an inner layer 15 from the outside to the inside; the outer layer 11, the heat insulation layer 12, the self-healing flexible carbon-based electric heating film 13, the flexible carbon-based thermal conductive insulating layer 14 and the inner layer 15 are connected together by stitches; an elastic band 2 is installed inside the cuff of the glove body 1 for warmth preservation and tightness, a battery bag 3 is provided at the cuff of the glove body 1, the battery bag 3 is an elastic waterproof fabric, a 4 is provided on one side of the battery bag 3 for easy access, a battery 5 is provided inside the battery bag 3, and the battery 5 is a rechargeable battery, a temperature control module 6 is provided on the back of the glove body 1, the temperature control module 6 is provided with a switch and a temperature adjustment button, and the battery 5 and the self-healing flexible carbon-based electric heating film 13 are respectively connected to the temperature control module 6 through wires.

[0079] The self-healing flexible carbon-based electric heating film 13 is prepared from the following components in parts by weight: 33 parts of polyvinyl alcohol, 33 parts of poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid), 6 parts of polyethylene glycol 200, 6 parts of leaf-shaped carbon nanotubes, 4 parts of borax decahydrate, and 55 parts of a mixed solution of methanol and deionized water in a mass ratio of 1:1.

[0080] In this embodiment, the mass ratio of polyvinyl alcohol to poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) is 1:1.

[0081] The preparation method of leaf-shaped carbon nanotubes in this embodiment is as follows: in parts by weight, 8 parts of sodium nitrate and 70 parts of concentrated sulfuric acid are mixed evenly in a beaker at 4°C, and then 30 parts of multi-walled carbon nanotubes and 8 parts of potassium permanganate are added and stirred for 3 hours, and then the beaker is heated to 32°C and stirred for 42 minutes, and then 100 parts of deionized water are added drop by drop. After the addition is completed, the mixed solution is heated to 92°C, and the stirring reaction is continued for 18 minutes. Subsequently, 3% hydrogen peroxide is dripped into the mixed solution until gas stops being generated, and the product is collected by vacuum filtration, and then the filtered product is washed three times with deionized water, and each washing needs to be completely submerged with deionized water. Finally, the washed product is thoroughly dried in a vacuum drying oven at room temperature to obtain leaf-shaped carbon nanotubes.

[0082] The preparation method of the flexible carbon-based thermally conductive insulating layer 14 is as follows: by weight, 4 to 9 parts of fluorinated graphene and 100 parts of N-methylpyrrolidone are ultrasonically treated for 1 to 2 hours to obtain a fluorinated graphene suspension for use. Then, 10 to 16 parts of polyvinyl alcohol and 80 to 120 parts of deionized water are mixed and heated to 70 to 85°C, and stirred for 5 to 10 minutes to obtain a polyvinyl alcohol aqueous solution for use. Then, the uniformly dispersed fluorinated graphene suspension is vacuum filtered to remove N-methylpyrrolidone to obtain a carbon-based film, and then the polyvinyl alcohol aqueous solution is poured on the carbon-based film in three times, and the polyvinyl alcohol is infiltrated into the carbon-based film under vacuum pressure by vacuum filtration. Then, after the filtered carbon-based film is completely dried in a vacuum drying oven, the carbon-based film is hot-pressed at a temperature of 200 to 230°C and a pressure of 5 to 20 MPa for 5 to 10 minutes to finally obtain a flexible carbon-based thermally conductive insulating layer 14.

[0083] The preparation method of fluorinated graphene in this embodiment is as follows: by weight, 3 to 6 parts of graphene oxide and 30 to 60 parts of polyvinylidene fluoride are separated in a crucible by a copper mesh, with graphene oxide on the top and polyvinylidene fluoride on the bottom, and heated to 350 to 400° C. in an air environment, and kept warm for 2 to 4 hours to obtain a crude fluorinated graphene product, and then the crude fluorinated graphene product is washed three times with N-methylpyrrolidone, each washing needs to completely submerge the crude fluorinated graphene product, and finally dried completely in a vacuum drying phase at room temperature to obtain fluorinated graphene.

[0084] The preparation method of fluorinated graphene in this embodiment is as follows: by weight, 5 parts of graphene oxide and 55 parts of polyvinylidene fluoride are separated in a crucible by a copper mesh, with graphene oxide on the top and polyvinylidene fluoride on the bottom, and heated to 388 in an air environment and kept warm for 4 hours to obtain a crude fluorinated graphene product, and then the crude fluorinated graphene product is washed three times with N-methylpyrrolidone, each washing needs to completely submerge the crude fluorinated graphene product, and finally dried completely in a vacuum drying phase at room temperature to obtain fluorinated graphene.

[0085] In this embodiment, the fluorinated graphene contains 7% fluorine atom.

[0086] In this embodiment, the outer layer 11 is a fluorinated polyurethane fiber membrane, and its preparation method is as follows: after evenly mixing 3 parts of silver nitrate and 100 parts of dimethylacetamide by weight, 22 parts of fluorinated polyurethane prepolymer are added and stirred at 270rpm for 5h to obtain a mixed solution, which is then fed into a syringe with a capillary tip, the anode of the high-voltage power supply is connected to the syringe needle tip, and the cathode is connected to the floor drum. The fluorinated polyurethane fiber membrane is prepared by an electrospinning process, wherein the process parameters of the electrospinning are: an applied voltage of 47kV, a constant infusion rate of 2mL / h, a receiving distance of 23cm, an ambient temperature of 23°C, and a relative humidity of 77%.

[0087] The preparation method of the fluorinated polyurethane prepolymer in this embodiment is as follows: in parts by weight, 15 parts of polytetrahydrofuran, 26 parts of 4,4'-methylenebis(phenyl isocyanate) and 22 parts of dimethylformamide are added to a four-necked flask under a nitrogen environment, and stirred at 200 rpm for 44 minutes at 61°C to obtain a transparent and uniform solution, and then 3 parts of triethylene glycol chain extender are added thereto, and the stirring reaction is continued at 65°C for 2 hours, and finally 18 parts of perfluorobutylethanol and 10 parts of dimethylformamide are added to the flask, and stirring is continued for 3 hours to obtain a fluorinated polyurethane prepolymer.

[0088] In this embodiment, the heat insulating layer 12 is a polyimide aerogel, and its preparation method is as follows: in parts by weight, at 0°C, 6 parts of 4,4'-diaminodiphenyl ether, 6 parts of pyromellitic anhydride and 100 parts of N-methylpyrrolidone are mixed evenly, 6 parts of short-cut polyimide nanofibers are added, and then stirred at 370 rpm for 4 hours to obtain a uniformly dispersed solution, and then 37 parts of propionic anhydride and 37 parts of pyridine are added and stirred thoroughly, and then the solution is cast into a polytetrafluoroethylene mold with a scraper. After gelation, polyimide aerogel is obtained.

[0089] The preparation method of short-cut polyimide nanofibers in this embodiment is as follows: 13 parts of 4,4'-diaminodiphenyl ether, 13 parts of pyromellitic anhydride and 150 parts of dimethylacetamide are mixed evenly by weight and added into an electrospinning syringe to obtain polyimide fibers by an electrospinning process, wherein the process parameters of the electrospinning are as follows: the spinning voltage is 98 kV and the electrospinning speed is 2 mL / h. After the spinning is completed, the fibers are treated at 320°C for 2 hours to obtain polyimide nanofibers, and finally the polyimide nanofibers are cut into short-cut polyimide nanofibers with a cutter.

[0090] In this embodiment, the length of the short-cut polyimide nanofibers is 37 μm.

[0091] In this embodiment, the inner layer 15 is woven from modal fibers.

[0092] Example 4

[0093] See also Figure 1-2 The present invention provides a technical solution: a heating glove based on a flexible carbon-based composite film, comprising a glove body 1, the glove body 1 is composed of an outer layer 11, a heat insulation layer 12, a self-healing flexible carbon-based electric heating film 13, a flexible carbon-based thermal conductive insulating layer 14 and an inner layer 15 from the outside to the inside; the outer layer 11, the heat insulation layer 12, the self-healing flexible carbon-based electric heating film 13, the flexible carbon-based thermal conductive insulating layer 14 and the inner layer 15 are connected together by stitches; an elastic band 2 is installed inside the cuff of the glove body 1 for warmth preservation and tightness, a battery bag 3 is provided at the cuff of the glove body 1, the battery bag 3 is an elastic waterproof fabric, a 4 is provided on one side of the battery bag 3 for easy access, a battery 5 is provided inside the battery bag 3, and the battery 5 is a rechargeable battery, a temperature control module 6 is provided on the back of the glove body 1, the temperature control module 6 is provided with a switch and a temperature adjustment button, and the battery 5 and the self-healing flexible carbon-based electric heating film 13 are respectively connected to the temperature control module 6 through wires.

[0094] The self-healing flexible carbon-based electric heating film 13 is prepared from the following components in parts by weight: 235 parts of polyvinyl alcohol, 35 parts of poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid), 9 parts of polyethylene glycol 200, 7 parts of leaf-shaped carbon nanotubes, 5 parts of borax decahydrate, and 60 parts of a mixed solution of methanol and deionized water in a mass ratio of 1:1.

[0095] The preparation method of leaf-shaped carbon nanotubes in this embodiment is as follows: in parts by weight, 10 parts of sodium nitrate and 80 parts of concentrated sulfuric acid are mixed evenly in a beaker at 5°C, and then 35 parts of multi-walled carbon nanotubes and 10 parts of potassium permanganate are added and stirred for 4 hours, and then the beaker is heated to 35°C and stirred for 45 minutes, and then 100 parts of deionized water are added drop by drop. After the addition is completed, the mixed solution is heated to 95°C, and the stirring reaction is continued for 20 minutes. Subsequently, 3% hydrogen peroxide is dripped into the mixed solution until the gas stops being generated, and the product is collected by vacuum filtration, and then the filtered product is washed three times with deionized water, and each washing needs to completely submerge the filtered product with deionized water, and finally the washed product is thoroughly dried in a vacuum drying oven at room temperature to obtain leaf-shaped carbon nanotubes.

[0096] The preparation method of the flexible carbon-based thermally conductive insulating layer 14 is as follows: by weight, 9 parts of fluorinated graphene and 100 parts of N-methylpyrrolidone are ultrasonically treated for 2 hours to obtain a fluorinated graphene suspension for use. Then, 16 parts of polyvinyl alcohol and 120 parts of deionized water are mixed and heated to 85°C, and stirred for 10 minutes to obtain a polyvinyl alcohol aqueous solution for use. Then, the uniformly dispersed fluorinated graphene suspension is vacuum filtered to remove N-methylpyrrolidone to obtain a carbon-based film, and then the polyvinyl alcohol aqueous solution is poured on the carbon-based film in three times. By vacuum filtration, polyvinyl alcohol is infiltrated into the carbon-based film under vacuum pressure conditions, and then the filtered carbon-based film is completely dried in a vacuum drying oven, and then the carbon-based film is hot-pressed at a temperature of 230°C and a pressure of 20MPa for 10 minutes to finally obtain a flexible carbon-based thermally conductive insulating layer 14.

[0097] The preparation method of fluorinated graphene in this embodiment is as follows: by weight, 6 parts of graphene oxide and 60 parts of polyvinylidene fluoride are separated in a crucible by a copper mesh, with graphene oxide on the top and polyvinylidene fluoride on the bottom, and heated to 400°C in an air environment and kept warm for 4 hours to obtain a crude fluorinated graphene product, and then the crude fluorinated graphene product is washed three times with N-methylpyrrolidone, each washing needs to completely submerge the crude fluorinated graphene product, and finally dried completely in a vacuum drying phase at room temperature to obtain fluorinated graphene.

[0098] In this embodiment, the fluorinated graphene contains 7.5% fluorine atoms.

[0099] In this embodiment, the outer layer 11 is a fluorinated polyurethane fiber membrane, and its preparation method is as follows: after evenly mixing 4 parts of silver nitrate and 100 parts of dimethylacetamide by weight, 30 parts of fluorinated polyurethane prepolymer are added and stirred at 350 rpm for 6 hours to obtain a mixed solution, which is then fed into a syringe with a capillary tip, the anode of the high-voltage power supply is connected to the syringe needle tip, and the cathode is connected to the floor drum. The fluorinated polyurethane fiber membrane is prepared by an electrospinning process, wherein the process parameters of the electrospinning are: an applied voltage of 50 kV, a constant infusion rate of 2.5 mL / h, a receiving distance of 25 cm, an ambient temperature of 25°C, and a relative humidity of 80%.

[0100] The preparation method of the fluorinated polyurethane prepolymer in this embodiment is as follows: in parts by weight, 18 parts of polytetrahydrofuran, 30 parts of 4,4'-methylenebis(phenyl isocyanate) and 25 parts of dimethylformamide are added to a four-necked flask under a nitrogen environment, and stirred at 240 rpm for 60 minutes at 65°C to obtain a transparent and uniform solution, and then 5 parts of triethylene glycol chain extender are added thereto, and the stirring reaction is continued at 70°C for 3 hours, and finally 22 parts of perfluorobutylethanol and 14 parts of dimethylformamide are added to the flask, and stirring is continued for 4 hours to obtain a fluorinated polyurethane prepolymer.

[0101] In this embodiment, the heat insulating layer 12 is a polyimide aerogel, and its preparation method is as follows: in parts by weight, at 0°C, 9 parts of 4,4'-diaminodiphenyl ether, 9 parts of pyromellitic anhydride and 100 parts of N-methylpyrrolidone are mixed evenly, 8 parts of short-cut polyimide nanofibers are added, and then stirred at 450 rpm for 60 hours to obtain a uniformly dispersed solution, and then 45 parts of propionic anhydride and 45 parts of pyridine are added and stirred thoroughly, and then the solution is cast into a polytetrafluoroethylene mold with a scraper. After gelation, a polyimide aerogel is obtained.

[0102] The preparation method of short-cut polyimide nanofibers in this embodiment is as follows: 16 parts of 4,4'-diaminodiphenyl ether, 16 parts of pyromellitic anhydride and 150 parts of dimethylacetamide are mixed evenly by weight and added into an electrospinning syringe to obtain polyimide fibers by an electrospinning process, wherein the process parameters of the electrospinning are as follows: the spinning voltage is 105 kV and the electrospinning speed is 3 mL / h. After the spinning is completed, the fibers are treated at 350°C for 3 hours to obtain polyimide nanofibers, and finally the polyimide nanofibers are cut into short-cut polyimide nanofibers with a cutter.

[0103] In this embodiment, the length of the short-cut polyimide nanofibers is 60 μm.

[0104] In this embodiment, the inner layer 15 is woven from modal fibers.

[0105] Example 5

[0106] It is basically the same as Example 1, except that the leaf-shaped carbon nanotubes added to the self-healing flexible carbon-based electric heating film 13 are 7 parts.

[0107] Comparative Example 1

[0108] It is basically the same as Example 1, except that original multi-walled carbon nanotubes are added to prepare the self-healing flexible carbon-based electric heating film instead of leaf-shaped carbon nanotubes.

[0109] Comparative Example 2

[0110] It is basically the same as Example 1, except that no borax decahydrate is added in the preparation of the self-healing flexible carbon-based electric heating film.

[0111] Characterization Tests:

[0112] Figure 3 Transmission electron microscope photos show the structure of leaf-shaped carbon nanotubes in the self-healing flexible carbon-based electrothermal film of the gloves in Example 1 of the present invention. The darker ones are similar to petioles, and the lighter ones are similar to leaves, confirming its successful preparation.

[0113] Figure 4 The self-healing flexible carbon-based electrothermal film of the gloves prepared in Example 1 of the present invention is used as a conductor of a light-emitting diode in a series circuit when it is not stretched. Figure 5 The self-healing flexible carbon-based electrothermal film of the glove prepared in Example 1 of the present invention is in a stretched state and is used as a conductor of a light-emitting diode in a series circuit. After rigorous experimental testing of the self-healing flexible carbon-based electrothermal film prepared in Example 1 of the present invention, the film's ability to serve as a conductive medium for the light-emitting diode in the series circuit is not affected after undergoing stretching deformation, and it can still ensure the effective transmission of current, thereby driving the diode to emit light normally. This experimental result conclusively proves that the film has excellent conductivity stability under normal strain (especially in the stretched state), and its electrothermal function is maintained. Figure 4 and Figure 5 The comparative analysis further strengthened this discovery, revealing the robustness of the conductive network of the film during deformation and the persistence of its electrothermal effect, providing important experimental basis and theoretical support for the research of thermoelectric films for wearable heating gloves.

[0114] like Figure 6 As shown in Figure 1, when the film was cut off when it was used as a conductor of a light-emitting diode in a series circuit, the circuit was immediately interrupted and the diode stopped emitting light, which verified the impact of the destruction of the circuit integrity on the conductive properties. However, after the film was kept in a moisturizing state for 24 hours after contact, self-healing occurred (as shown in Figure 1). Figure 7As shown in the figure, the film successfully healed itself and was connected to the circuit as a wire again, making the diode emit light again. This remarkable phenomenon not only directly proves that the film has the ability to self-repair fractures and restore its conductive function, but also reflects its high reliability in autonomously restoring integrity and performance after damage. Therefore, the conclusions of this study strongly support the potential value of self-healing flexible carbon-based electrothermal films in glove applications that require high durability and easy maintenance.

[0115] Performance Test:

[0116] Mechanical properties test: The mechanical properties test of the self-healing flexible carbon-based electric heating film was conducted using a microcomputer-controlled universal material testing machine (SANS-CMT4204) at a preset tensile rate of 2 mm / min. During the test, the film sample was precisely installed between the fixtures of the testing machine to ensure the consistency of the test environment. The tensile strength and elongation at break of the film were evaluated through the automatically recorded stress-strain curve. These parameters directly reflect the strength and flexibility of the film when subjected to tension.

[0117] Electrothermal performance: The electrothermal performance test of the self-healing flexible carbon-based electrothermal film adopts a professional thermoelectric parameter test system (ADVANCE RIKO Inc., Japan). The system can accurately measure the conductivity and Seebeck coefficient of the film, so as to comprehensively evaluate its electrothermal conversion efficiency and thermoelectric properties. During the test, the film sample is placed in a standard test environment to ensure the consistency of the test conditions. A stable current or temperature gradient is applied by the system, and the voltage change or temperature difference across the film is measured to calculate the conductivity and Seebeck coefficient. These parameters directly reflect the conductive properties and thermoelectric conversion capabilities of the film, and provide important performance indicators and scientific basis for the application of self-healing flexible carbon-based electrothermal films in heating, temperature control and energy conversion.

[0118] Self-healing ability: In order to evaluate the self-healing ability of the self-healing flexible carbon-based electric heating film, we performed the following test process: First, use a sharp blade to accurately cut the film sample; then, use a special clamp to clamp the cut ends tightly together to ensure that they maintain a stable contact state; then, place this combination in a humid environment for 24 hours to simulate and promote the self-healing process; finally, the film sample is tested for thermoelectric performance again, focusing on key indicators such as its conductivity and Seebeck coefficient, so as to comprehensively evaluate the degree of recovery of its self-healing ability to electric and thermal performance. At the same time, the same method is used to test the mechanical properties after self-healing, focusing on evaluating its tensile strength and elongation.

[0119] The properties of the self-healing flexible carbon-based electric heating films of Examples 1 to 5 and Comparative Examples 1 to 2 are summarized in Table 2.

[0120] Table 2 Performance summary of self-healing flexible carbon-based electric heating films of Examples 1 to 5 and Comparative Examples 1 to 2

[0121]

[0122]

[0123] The main difference between Comparative Example 1 and Example 1 is whether the carbon nanotubes are original multi-walled carbon nanotubes or leaf-shaped carbon nanotubes. As can be seen from Table 2, the use of leaf-shaped carbon nanotubes significantly increases the tensile strength and electrothermal performance of the self-healing flexible carbon-based electrothermal film. This is because the design of leaf-shaped carbon nanotubes achieves multiple advantages: its unique overall structural design is conducive to the smooth conduction of electrons and phonons inside the material, thereby greatly improving the thermal and electrical conductivity of the material; at the same time, the multi-level structure significantly increases the specific surface area of ​​the material, provides more contact area, is conducive to the uniform dispersion and effective transmission of external forces and stresses inside the material, and enhances the mechanical properties of the material; in addition, the leaf part can produce deformation, absorb and buffer impact energy, and the petiole part plays a stable support and load transfer role, which together improves the comprehensive performance of the material, including good elasticity and impact resistance. These advantages make leaf-shaped carbon nanotubes perform better than original multi-walled carbon nanotubes in self-healing flexible carbon-based electrothermal films.

[0124] The main difference between Comparative Example 2 and Example 1 is whether borax decahydrate is added to the self-healing flexible carbon-based electric heating film. As can be seen from Table 2, the addition of borax decahydrate can significantly improve the self-healing ability of the self-healing flexible carbon-based electric heating film. This is because borax decahydrate plays a key role as a cross-linking agent in the film, undergoes a cross-linking reaction with the hydroxyl groups on the polyvinyl alcohol molecular chain, and forms a stable cross-linked structure. When the film is damaged by the outside world, this cross-linked structure can respond quickly, and promote the self-repair of the damaged area through rearrangement and cross-linking between molecules. Specifically, the addition of borax decahydrate enhances the interaction force between the polyvinyl alcohol molecular chains, so that when the film is damaged, it can use these interaction forces to rearrange the molecular chains and fill the damaged area, thereby achieving self-repair. In addition, by adjusting the content of borax decahydrate, the speed and effect of self-repair can be finely controlled to meet the needs of different application scenarios. Therefore, adding borax decahydrate is an effective means to enhance the self-healing ability of the self-healing flexible carbon-based electric heating film.

[0125] In summary, the electric heating gloves of the present invention use a self-healing flexible carbon-based electric heating film as the core, which combines the excellent conductivity of graphene and the excellent thermal conductivity of carbon nanotubes, not only achieving a double leap in electric heat conversion efficiency and thermal conductivity, but also significantly improving the durability and reliability of the gloves through the self-healing mechanism. The self-healing ability means that the gloves can automatically repair themselves when they suffer minor damage, reducing performance degradation or failure caused by damage, thereby extending the service life and reducing maintenance costs.

[0126] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that all equivalent structural changes made under the concept of the present invention and using the contents of the present invention specification and drawings should be covered within the scope of protection of the claims of the present invention.

Claims

1. A heating glove based on a flexible carbon-based composite film, characterized in that: The invention comprises a glove body (1), wherein the glove body (1) comprises, from the outside to the inside, an outer layer (11), a heat insulating layer (12), a self-healing flexible carbon-based electric heating film (13), a flexible carbon-based heat conductive insulating layer (14) and an inner layer (15); the outer layer (11), the heat insulating layer (12), the self-healing flexible carbon-based electric heating film (13), the flexible carbon-based heat conductive insulating layer (14) and the inner layer (15) are all connected together by stitching; an elastic band (2) is installed inside the cuff of the glove body (1) for warmth preservation and tight fit; the glove body A battery bag (3) is provided at the cuff of (1), the battery bag (3) is made of elastic waterproof fabric, a zipper (4) is provided on one side of the battery bag (3) for easy access, a storage battery (5) is provided inside the battery bag (3), the storage battery (5) is a rechargeable storage battery (5), the battery bag (3) is provided with a temperature control module (6), the temperature control module (6) is provided with a switch and a temperature adjustment button, the storage battery (5) and the self-healing flexible carbon-based electric heating film (13) are respectively connected to the temperature control module (6) through wires; The self-healing flexible carbon-based electric heating film (13) is prepared from the following components in parts by weight: 25-35 parts of polyvinyl alcohol, 25-35 parts of poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid), 4-9 parts of polyethylene glycol 200, 3-7 parts of leaf-shaped carbon nanotubes, 2-5 parts of borax decahydrate, and 40-60 parts of a mixed solution of methanol and deionized water in a mass ratio of 1:1; The preparation method of leaf-shaped carbon nanotubes is as follows: in parts by weight, at 0-5°C, 5-10 parts of sodium nitrate and 50-80 parts of concentrated sulfuric acid are mixed evenly in a beaker, then 20-35 parts of multi-walled carbon nanotubes and 4-10 parts of potassium permanganate are added and stirred for 2-4 hours, then the beaker is heated to 25-35°C and stirred for 30-45 minutes, then 100 parts of deionized water are added drop by drop, after the addition is completed, the mixed solution is heated to 85-95°C, and the stirring reaction is continued for 10-20 minutes, and then 3% hydrogen peroxide is dripped into the mixed solution until gas stops being generated, and the product is collected by vacuum filtration, and then the filtered product is washed three times with deionized water, and each washing needs to be completely submerged with deionized water. The filtered product is finally dried thoroughly in a vacuum drying oven at room temperature to obtain leaf-shaped carbon nanotubes.

2. A heating glove based on a flexible carbon-based composite film as claimed in claim 1, characterized in that: The preparation method of the flexible carbon-based thermally conductive insulating layer (14) is as follows: by weight, 4 to 9 parts of fluorinated graphene and 100 parts of N-methylpyrrolidone are ultrasonically treated for 1 to 2 hours to obtain a fluorinated graphene suspension for use; then 10 to 16 parts of polyvinyl alcohol and 80 to 120 parts of deionized water are mixed and heated to 70 to 85°C, and stirred for 5 to 10 minutes to obtain a polyvinyl alcohol aqueous solution for use; then the uniformly dispersed fluorinated graphene suspension is subjected to vacuum filtration to remove N-methylpyrrolidone to obtain a carbon-based film, and then the polyvinyl alcohol aqueous solution is poured onto the carbon-based film in three times, and the polyvinyl alcohol is infiltrated into the carbon-based film under vacuum pressure by vacuum filtration, and then the filtered carbon-based film is completely dried in a vacuum drying oven, and then the carbon-based film is hot-pressed at a temperature of 200 to 230°C and a pressure of 5 to 20 MPa for 5 to 10 minutes to finally obtain a flexible carbon-based thermally conductive insulating layer (14).

3. A heating glove based on a flexible carbon-based composite film as claimed in claim 2, characterized in that: The preparation method of the fluorinated graphene is as follows: by weight, 3 to 6 parts of graphene oxide and 30 to 60 parts of polyvinylidene fluoride are separated in a crucible through a copper mesh, with graphene oxide on the top and polyvinylidene fluoride on the bottom, and heated to 350 to 400° C. in an air environment, and kept warm for 2 to 4 hours to obtain a crude fluorinated graphene product, and then the crude fluorinated graphene product is washed three times with N-methylpyrrolidone, each washing needs to completely submerge the crude fluorinated graphene product, and finally dried completely in a vacuum drying oven at room temperature to obtain the fluorinated graphene; The mass ratio of the graphene oxide to polyvinylidene fluoride is 1:

10.

4. A heating glove based on a flexible carbon-based composite film as claimed in claim 2 or 3, characterized in that: The fluorinated graphene contains 5-7.5% fluorine atoms.

5. The heating glove based on the flexible carbon-based composite film according to claim 1, characterized in that: The outer layer (11) is a fluorinated polyurethane fiber membrane, and its preparation method is as follows: after 2 to 4 parts of silver nitrate and 100 parts of dimethylacetamide are mixed evenly by weight, 15 to 30 parts of fluorinated polyurethane prepolymer are added and stirred at 200 to 350 rpm for 4 to 6 hours to obtain a mixed solution, which is then fed into a syringe with a capillary tip, the anode of a high-voltage power supply is connected to the syringe needle tip, and the cathode is connected to a floor drum, and the fluorinated polyurethane fiber membrane is prepared by an electrospinning process, wherein the process parameters of the electrospinning are: an applied voltage of 40 to 50 kV, a constant infusion rate of 1 to 2.5 mL / h, a receiving distance of 20 to 25 cm, an ambient temperature of 20 to 25 °C, and a relative humidity of 70 to 80%.

6. A heating glove based on a flexible carbon-based composite film as claimed in claim 5, characterized in that: The preparation method of the fluorinated polyurethane prepolymer is as follows: in parts by weight, in a nitrogen environment, 10 to 18 parts of polytetrahydrofuran, 20 to 30 parts of 4,4'-methylenebis(phenyl isocyanate) and 18 to 25 parts of dimethylformamide are added to a four-necked flask, stirred at 160 to 240 rpm for 30 to 60 minutes at 55 to 65°C to obtain a transparent and uniform solution, then 2 to 5 parts of triethylene glycol chain extender are added thereto, and the stirring reaction is continued at 60 to 70°C for 1 to 3 hours, and finally 15 to 22 parts of perfluorobutylethanol and 7 to 14 parts of dimethylformamide are added to the flask, and the stirring is continued for 2 to 4 hours to obtain a fluorinated polyurethane prepolymer.

7. The heating glove based on the flexible carbon-based composite film according to claim 1, characterized in that: The heat insulating layer (12) is a polyimide aerogel, and its preparation method is as follows: in parts by weight, at 0°C, 4 to 9 parts of 4,4'-diaminodiphenyl ether, 4 to 9 parts of pyromellitic anhydride and 100 parts of N-methylpyrrolidone are mixed evenly, 4 to 8 parts of short-cut polyimide nanofibers are added, and then stirred at 300 to 450 rpm for 3 to 6 hours to obtain a uniformly dispersed solution, and then 30 to 45 parts of propionic anhydride and 30 to 45 parts of pyridine are added and stirred thoroughly, and then the solution is cast into a polytetrafluoroethylene mold with a scraper to obtain a polyimide aerogel after gelation.

8. A heating glove based on a flexible carbon-based composite film as claimed in claim 7, characterized in that: The preparation method of the short-cut polyimide nanofiber is as follows: 10 to 16 parts of 4,4'-diaminodiphenyl ether, 10 to 16 parts of pyromellitic anhydride and 150 parts of dimethylacetamide are mixed evenly by weight, and then added into an electrospinning syringe, and polyimide fibers are obtained by an electrospinning process, wherein the electrospinning process parameters are: spinning voltage of 90 to 105 kV, electrospinning speed of 1.5 to 3 mL / h, and after spinning, the fibers are treated at 300 to 350° C. for 1 to 3 hours to obtain polyimide nanofibers, and finally the polyimide nanofibers are cut into short-cut polyimide nanofibers by a cutter; The length of the short-cut polyimide nanofibers is 10-60 μm.

9. The heating glove based on the flexible carbon-based composite film according to claim 1, characterized in that: The inner layer (15) is woven from modal fibers.

Citation Information

Patent Citations

  • Rechargeable warm glove

    CN204483158U

  • Heteroatom doped leaf-shaped carbon nanometer aerogel material and preparation method and application thereof

    CN104437278A

  • Carbon nanotube electric heating assembly and application thereof, and electric heating clothes

    CN108366440A